Optimal Design of a Semi Grid-Connected PV System for a Site in Lwak, Kenya Using HOMER - Kakande, Josephine Nakato; Philipo, Godiana Hagile; Krauter, Stefan (Proceedings of the 8th World Conference on Photovoltaik Energy Conversion)

Neural Network-Based Demand-Side Management in a Stand-Alone Solar PV-Battery Microgrid Using Load-Shifting and Peak-Clipping - Philipo, Godiana Hagile; Kakande, Josephine Nakato; Krauter, Stefan (Energies)
Due to failures or even the absence of an electricity grid, microgrid systems are becoming popular solutions for electrifying African rural communities. However, they are heavily stressed and complex to control due to their intermittency and demand growth. Demand side management (DSM) serves as an option to increase the level of flexibility on the demand side by scheduling users’ consumption patterns profiles in response to supply. This paper proposes a demand-side management strategy based on load shifting and peak clipping. The proposed approach was modelled in a MATLAB/Simulink R2021a environment and was optimized using the artificial neural network (ANN) algorithm. Simulations were carried out to test the model’s efficacy in a stand-alone PV-battery microgrid in East Africa. The proposed algorithm reduces the peak demand, smoothing the load profile to the desired level, and improves the system’s peak to average ratio (PAR). The presence of deferrable loads has been considered to bring more flexible demand-side management. Results promise decreases in peak demand and peak to average ratio of about 31.2% and 7.5% through peak clipping. In addition, load shifting promises more flexibility to customers.
Keywords: Energy (miscellaneous); Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment; Electrical and Electronic Engineering; Control and Optimization; Engineering (miscellaneous); Building and Construction

Neural Network-Based Demand-Side Management in a Stand-Alone Solar PV-Battery Microgrid Using Load-Shifting and Peak-Clipping - Philipo, Godiana Hagile; Kakande, Josephine Nakato; Krauter, Stefan (Energies)
Due to failures or even the absence of an electricity grid, microgrid systems are becoming popular solutions for electrifying African rural communities. However, they are heavily stressed and complex to control due to their intermittency and demand growth. Demand side management (DSM) serves as an option to increase the level of flexibility on the demand side by scheduling users’ consumption patterns profiles in response to supply. This paper proposes a demand-side management strategy based on load shifting and peak clipping. The proposed approach was modelled in a MATLAB/Simulink R2021a environment and was optimized using the artificial neural network (ANN) algorithm. Simulations were carried out to test the model’s efficacy in a stand-alone PV-battery microgrid in East Africa. The proposed algorithm reduces the peak demand, smoothing the load profile to the desired level, and improves the system’s peak to average ratio (PAR). The presence of deferrable loads has been considered to bring more flexible demand-side management. Results promise decreases in peak demand and peak to average ratio of about 31.2% and 7.5% through peak clipping. In addition, load shifting promises more flexibility to customers.
Keywords: Energy (miscellaneous); Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment; Electrical and Electronic Engineering; Control and Optimization; Engineering (miscellaneous); Building and Construction

Einfluss von Steilaufstellung, Nachführung und Einsatz bifazialer PV-Module auf den Speicherbedarf und die Kosten einer 100% EE-Versorgung Deutschlands - Krauter, Stefan; Khatibi, Arash (Tagungsband des 36. PV-Symposium, 18.-26 Mai 2021, online, ISBN 978-3-948176-14-3, S. 301-304.)

Comparison and Validation of Irradiance Data: Satellite Meteorological Dataset MERRA-2 vs. Meteonorm and German Weather Service (DWD) - Khatibi, Arash; Krauter, Stefan (Proceedings of the 38th European Photovoltaic Solar Energy Conference and Exhibition (EUPVSEC 2021))
Access to precise meteorological data is crucial to be able to plan and install renewable energy systems such as solar power plants and wind farms. In case of solar energy, knowledge of local irradiance and air temperature values is very important. For this, various methods can be used such as installing local weather stations or using meteorological data from different organizations such as Meteonorm or official Deutscher Wetterdienst (DWD). An alternative is to use satellite reanalysis datasets provided by organizations like the National Aeronautics and Space Administration (NASA) and European Centre for Medium-Range Weather Forecasts (ECMWF). In this paper the “Modern-Era Retrospective analysis for Research and Applications” dataset version 2 (MERRA-2) will be presented, and its performance will be evaluated by comparing it to locally measured datasets provided by Meteonorm and DWD. The analysis shows very high correlation between MERRA-2 and local measurements (correlation coefficients of 0.99) for monthly global irradiance and air temperature values. The results prove the suitability of MERRA-2 data for applications requiring long historical data. Moreover, availability of MERRA-2 for the whole world with an acceptable resolution makes it a very valuable dataset.
Keywords: Energy potential estimation; Photovoltaic; Solar radiation; Temperature measurement; Satellite data; Meteonorm; MERRA-2; DWD

Module-Inverters (Microinverters): Influence of Module Size on Conversion Efficiencies and Energy Yields - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 38th European Photovoltaic Solar Energy Conference and Exhibition (EU PVSEC 2021))
Efficiencies and energy yields of microinverters available on the market during 2014‒2021 have been measured, compared, and ranked. Conversion efficiencies as a function of load have been measured indoors with high accuracy and ranked according to Euro- and CEC weightings. Energy yields have been measured outdoors via identical and calibrated crystalline silicon PV modules of 215 Wp (until 2020) and 360 Wp (starting 2021). Inverters with two inputs have been fed by two of those modules. DC input, AC power output and energy yield of each microinverter have been recorded by individual calibrated electricity meters. CEC and EU efficiency rankings have been computed and compared. To assess the influence of PV module size, two extremes have been investigated: A rather small module with 215 Wp - as it has been used 10 years ago, and a brand-new module (2021) offering 360 Wp. Both types of modules contain 60 solar cells in series connection. Appling the low-power modules, the challenge for the different micro-inverters has been during weak-light conditions, using the high-power modules, some inverters temporarily reach their power limits and yield is reduced. A method using a reference configuration of inverter & module and a linear equation y = ax + b resulting in the actual yield, any module & inverter configuration can be characterized by just the coefficients a and b.
Keywords: AC-modules; Microinverter; Power Conditioning; Efficiency; Yield; PV module size; saturation; performance

Validation and Performance of Satellite Meteorological Dataset MERRA-2 for Solar and Wind Applications - Khatibi, Arash; Krauter, Stefan (Energies)
Fast-growing energy demand of the world makes the researchers focus on finding new energy sources or optimizing already-developed approaches. For an efficient use of solar and wind energy in an energy system, correct design and sizing of a power system is of high importance and improving or optimizing the process of data obtaining for this purpose leads to higher performance and lower cost per unit of energy. It is essential to have the most precise possible estimation of solar and wind energy potential and other local weather parameters in order to fully feed the demand and avoid extra costs. There are various methods for obtaining local data, such as local measurements, official organizational data, satellite obtained, and reanalysis data. In this paper, the Modern-Era Retrospective analysis for Research and Applications dataset version 2 (MERRA-2) dataset provided by NASA is introduced and its performance is evaluated by comparison to various locally measured datasets offered by meteorological institutions such as Meteonorm and Deutscher Wetterdienst (DWD, or Germany’s National Meteorological Service) around the world. After comparison, correlation coefficients from 0.95 to 0.99 are observed for monthly global horizontal irradiance values. In the case of air temperature, correlation coefficients of 0.99 and for wind speed from 0.81 to 0.99 are observed. High correlation with ground measurements and relatively low errors are confirmed, especially for irradiance and temperature values, that makes MERRA-2 a valuable dataset, considering its world coverage and availability.
Keywords: Solar irradiance; MERRA 2; Meteonorm; DWD

Load Data Acquisition in Rural East Africa for the Layout of Microgrids and Demand–Side–Management Measures - Kakande, Josephine Nakato; Philipo, Godiana Hagile; Krauter, Stefan (Proceedings of the 38th European Photovoltaic Solar Energy Conference and Exhibition (EUPVSEC 2021))
With its growing population and industrialization, DREs, and solar technologies in particular, provide a sustainable means of bridging the current energy deficit in Africa, increasing supply reliability and meeting future demand. Data acquisition and data management systems allow real time monitoring and control of energy systems as well as performance analysis. However commercial data acquisition systems often have cost implications that are prohibitive for small PV systems and installations in developing countries. In this paper, a multi-user, multi-purpose microgrid database system is designed and implemented. MAVOWATT 270 power quality analyzers by GOSSEN METRAWATT, raspberry pi modules and sensors are used for measuring, recording and storing electrical and meteorological data in East Africa. Socio-economic data is also stored in the database. The designed system employs open source software and hardware solutions which are best suited to developing regions like East Africa due to the lower cost implications. The expected results promise a comprehensive database covering different electro-technical and socio-economic parameters useful for optimal design of microgrid systems.
Keywords: Art-D; Afrika; Demand side management; MySQL; Raspberry pi; Data acquisition

Projekt Art-D Grids: Nachhaltige und stabile Microgrids in Afrika - eine Plattform für Forschung und Lehre für die Entwicklung - Krauter, Stefan; Böcker, Joachim; Freitag, Christine; Hehenkamp, Burkhard; Hilleringmann, Ulrich; Temmen, Katrin; Klaus, Tobias; Rohrer, Nicolaus; Lehmann, Sven (Tagungsband des 36. PV-Symposiums, 18.-26 Mai 2021)
Keywords: Art-D; Afrika; Resilienz; Resilience; Grid stability; robustness; microgrids

Micro-Inverters: An Update of Comparison of Conversion Efficiencies and Energy Yields - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the EUPVSEC 2020)
Efficiencies and energy yields of microinverters available on the market during 2014‒2020 have been measured, compared, and ranked. Conversion efficiencies as a function of load have been measured indoors with high accuracy and ranked according to Euro- and CEC weightings. Energy yields have been measured outdoors via identical and calibrated crystalline silicon PV modules of 215 Wp each. Inverters with two inputs have been fed by two of those modules. DC input, AC power output and energy yield of each micro-inverter have been recorded by individual calibrated electricity meters. Apparently, some inverters have been optimized for high irradiance levels and ranked better at the CEC efficiency ranking, others performed very well also at low irradiance levels, thus ranking higher at in the EU efficiency ranking. Efficiency ranks are slightly deviating from rankings by energy yield measurements. At one inverter, a slow MPPT algorithm that barely could follow quickly changing irradiance levels is most probably responsible for this effect. Another inverter switched off for a while after operation at high power, another one failed permanently. Apparently, some inverters are been optimized to show excellent datasheet ratings for EU- or CEC- efficiency. On the other hand, two inverters (each featuring two inputs) did not show an outstanding performance at the EU- and CEC-ratings but achieved leading ranks for AC energy yields. For the customer, AC yield is a major performance indicator of a microinverter and should be included in the datasheet.

Einfluss der Betriebstemperatur auf den Wirkungsgrad von Modul-Wechselrichtern für PV-Netzeinspeisungen - Krauter, Stefan; Bendfeld, Jörg (Tagungsband des 35. Symposiums für Photovoltaische Solarenergie, Kloster Banz, Bad Staffelstein (Deutschland))

Triggering Demand‒Side‒Management: Correlation of electricity prices, share of renewables, CO2‒contents, and grid‒frequency in the German electricity grid. - Krauter, Stefan; Zhang, L. (Proceedings of the 37th European Photovoltaic Solar Energy Conference, 07 - 11 September 2020.)
To provide a simple instrument to operate residential Load-Shifting or Demand-Side-Management systems, the measurement of the actual grid frequency seems to be an appropriate method. Due to the present inflexibility and the lack of sufficient throttling capabilities of lignite and nuclear power plants, a surplus of electricity generation occurs during periods of high wind and solar power generation. While the specific CO2- emission is decreasing then ‒ due to the increased share of Renewables, the grid frequency is increasing (to a certain limit). Using the grid frequency as an indicator to switch-on and off certain loads (loads that do not require power permanently (e.g. dishwashers, washing machines, dryers, fridges and freezers, heaters) could provide a simple, inexpensive demand-side management indicator to lower specific CO2‒emssions and costs (if a dynamic consumption tariff is available). To check the truthfulness of that hypothesis, the grid and frequency data of the German grid of the year 2018 have been collected and a the correlation between grid frequency, power surplus, share of renewables vs. CO2-contents and price at the European energy exchange (EEX) have been calculated. The results show: Correlation between frequency and share of renewables is quite low (r = 0.155) due to the fact that primary grid control quickly compensates deviations from the 50 Hz nominal frequency. There is a good anti-correlation (r = - 0.687) between the EEX‒prices and the share of renewables in the grid. Over the years, correlation between electricity trading prices (EEX) and CO2 emissions is quite good (r =0.665), within the one year (2018) that correlation almost doesn’t exist, possibly due to the inflexibility of the bulky lignite power plants that even operate at negative prices.
Keywords: Keywords: Load-Shifting; Demand-Side-Management; DSM; grid frequency; EEX; electricity trading prices; renewable share; flexibility; emissions; CO2

Reduction of required storage capacities for a 100% renewable energy supply in Germany, if new PV systems are installed with east-west tracking systems at increased elevation angles - Krauter, Stefan; Rustemovic, D.; Khatibi, Arash (Proceedings of the 37th European Photovoltaic Solar Energy Conference, 07 - 11 September 2020)
Due to the strong reduction of PV prices, storage plays a dominating role in overall system costs. A steeper elevation angle would result in a more balanced seasonal PV yield, at the cost of PV yield reductions during summer, but allowing reduced storage capacities. Additionally, the effect of a single-axis tracking system has been investigated, generating more electricity during the morning and evening hours, thus reducing daily storage requirements. The necessary PV size and storage capacities required for the German energy supply (1,500 TWh after electrification of all sectors) via 100% renewable energies and a 50% solar share have been calculated via the HOMER Pro software, considering the bridging of periods of "dark lulls“ in winter, using costs of 2030 (Table 1). Results: The increase of module elevation angles above the typical 30° leads to a reduction of investment and supply costs. The optimum is reached at a cost reduction of -1.5% for an elevation angle at the latitude of the installation site. An explanation is that high elevation angles are favorable for clear winter days, but not at all for the critical days with diffuse irradiance only, so the battery capacity must be increased. For the same reason, tracking systems do not offer any cost advantage (at least for the ones without an option for horizontal positioning during diffuse days).
Keywords: Energy Storage; PV system integration; Large Grid-connected PV systems; Simulation; Energy Supply Options

Elevated Temperatures Affecting Efficiency, Overall Performance and Energy Yield of PV Microinverters - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the EU PVSEC 2020)
During comparative measurements of different PV microinverters, two yield issues came up that could not be explored via conventional efficiency measurements, but do have a significant impact on electrical energy yield: First category of issues are either sluggish or nervously acting maximum–power–point–tracking devices, which lead to reduced energy yields. The other category of issues is thermal: As a first explanation for observed reduced energy yields, it has been assumed that the conversion efficiency degrades at higher operating temperatures. This matter has been investigated in this article: A change in conversion efficiency could not be observed for elevated operation temperatures up to 50°C, despite high-precision and repeated measurements. But it was found that some inverters temporarily interrupted (or entirely stopped) operation after long periods of running at high temperatures. Also, a reduction in potential maximum power output has been detected for those inverters. Summarizing: With a high degree of certainty it can be stated that those reported yield losses have been caused by the temporary shutdowns and power limitations of the inverters.
Keywords: AC-modules; Microinverter; Power Conditioning; Thermal Performance; Ventilation; Stability; Efficiency; Yield

Correlation of grid-frequency, electricity prices, share of Renewables and CO2-contents of German electricity grid to enable inexpensive triggering of Demand-Side-Management - Krauter, Stefan; Zhang, L. (Proceedings of the 47th IEEE Photovoltaic Specialists Conference (PVSC 47) 2020)
Due to the present inflexibility and the lack of sufficient throttling capabilities of lignite and nuclear power plants, a surplus of electricity generation occurs during periods of high wind and solar power generation in the German electricity grid. While the specific CO2-emission is decreasing then - due to the increased share of Renewables, the grid frequency should be increasing (to a certain limit). Using the grid frequency as an indicator to switch-on and -off certain loads (loads that do not require power permanently (e.g. dishwashers, washing machines, dryers, fridges and freezers, heaters) could provide a simple, inexpensive demand-side-management indicator to lower specific CO2-emissions and costs (if a dynamic consumption tariff is applied). To check the truthfulness of that hypothesis, the grid and frequency data of the German grid of the year 2018 have been collected and the correlations between grid frequency, share of renewables, CO2-contents, and actual price at the European energy exchange (EEX) have been calculated. The results show: Correlation between grid frequency and the share of renewables is quite low (r=0.155) due to the fact that primary grid control quickly compensates deviations from the 50 Hz nominal frequency. As expected, there is a good anti-correlation (r=-0.687) between the EEX-prices and the share of renewables in the grid. Over the years, correlation between electricity trading prices (EEX) and CO2 emissions is quite good (r=0.665), within the one year (2018) that correlation almost doesn't exist, possibly due to the inflexibility of the bulky lignite baseload power plants that even operate at negative prices.
Keywords: CO2; EEX; Grid frequency; DSM; electricity price; Renewable share

Comparison of Microinverters: Update on Rankings of Conversion Efficiencies and Energy Yields - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 47th IEEE Photovoltaic Specialists Conference (PVSC 47) JUNE 15 - AUGUST 21, 2020 VIRTUAL MEETING)
To compare efficiency and yield of many micro-inverters available on the world market in 2014-2020, an in- and outdoor test laboratory at the University of Paderborn has been set up. The inverters have been fed by identical and calibrated crystalline silicon PV modules of 215 Wp. To monitor accurately DC input, AC power output and energy yield, each of the micro-inverters has been equipped with a calibrated electricity meter. For micro-inverters requiring control units for grid-feeding that has been acquired also. The comparison covers efficiency-load characteristics as well as electrical energy yields. Purchase costs vary considerably between the models in comparison, sometimes inverter costs are higher than module costs, particularly if an additional grid-connection or interface device is needed for operation. The weighted conversion efficiency according to EU and CEC standards has been measured and calculated. While some inverters have been optimized for high irradiance levels, they ranked better at the CEC efficiency, others performed very well also for low irradiance levels, thus ranking higher at in the EU-efficiency tables. These results are deviating from the actual energy yield measurements, which show a slightly different ranking. At one inverter, an accurate, but very slow MPPT algorithm that barely could follow quickly changing irradiance levels could be the reason for this effect. Another inverter switched off after operation at high power output for a while. Apparently, some inverters are been optimized to show excellent EU and CEC efficiency ratings. Two of the inverters featuring two inputs did not show an exceptional performance at the EU- and CEC-ratings, but they achieved top ranks at the AC energy yield for the first years. For the customer, the AC yield is a major performance indicator of any microinverter and should be included in the datasheet.
Keywords: yield; AC; micro-inverter; MPPT; CEC rating; EU efficiency; Photovoltaic; Solar

Eignung der Netzfrequenz als Instrument der Entscheidungsfindung zur Auslösung von Lastverschiebungen bei niedrigen spezifischen CO2-Emissionen und EEX-Handelspreisen - Krauter, Stefan; Zhang, L. (Tagungsband des 35. Symposiums für Photovoltaische Solarenergie, Kloster Banz, Bad Staffelstein (Deutschland))

Probability of Correct Decision–Making at Triggering of Load-Shifting Intended for low CO2-intensity and low EEX trading-prices via simple Grid Frequency Monitoring - Krauter, Stefan; Zhang, L. (Proceedings of the 14th International Renewable Energy Storage Conference, Düsseldorf (Deutschland), 10.–12. März 2020 (verschoben: 16.–18. März 2021))

Entwicklung eines thermischen 1D-Simulationsmodells zur Bestimmung der Temperaturverteilung in Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny

Numerische Untersuchung der Temperaturverteilung in PCM-integrierten Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Kenig, Eugeny

Meteorological Data Forecast using RNN - Balluff, Stefan; Bendfeld, Jörg; Krauter, Stefan (Deep Learning and Neural Networks)
Gathering knowledge not only of the current but also the upcoming wind speed is getting more and more important as the experience of operating and maintaining wind turbines is increasing. Not only with regards to operation and maintenance tasks such as gearbox and generator checks but moreover due to the fact that energy providers have to sell the right amount of their converted energy at the European energy markets, the knowledge of the wind and hence electrical power of the next day is of key importance. Selling more energy as has been offered is penalized as well as offering less energy as contractually promised. In addition to that the price per offered kWh decreases in case of a surplus of energy. Achieving a forecast there are various methods in computer science: fuzzy logic, linear prediction or neural networks. This paper presents current results of wind speed forecasts using recurrent neural networks (RNN) and the gradient descent method plus a backpropagation learning algorithm. Data used has been extracted from NASA's Modern Era-Retrospective analysis for Research and Applications (MERRA) which is calculated by a GEOS-5 Earth System Modeling and Data Assimilation system. The presented results show that wind speed data can be forecasted using historical data for training the RNN. Nevertheless, the current set up system lacks robustness and can be improved further with regards to accuracy.

Numerical Investigation of the Temperature Distribution in PCM-integrated Solar Modules - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny (Chemical Engineering Transactions)

An Automated Solar-Biomass Hybrid Dryer System for Rural Communities in Ghana - Obeng-Akrofi, George; Oppong Akowuah, Joseph; Opoku-Agyemang, Gifty; Nkrumah, Isaac; Donkor, Micheal K. E.; Tamakloe, Reuben Y.; Ampong, Francis K.; Klaus, Tobias; Krauter, Stefan; Waldhoff, Maike; Olenberg, Alexander; Kenig, Eugeny (Proceedings of SWC2017/SHC2017)

Simple and effective methods to match photovoltaic power generation to the grid load profile for a PV based energy system. - Krauter, Stefan (Solar Energy)

Smart charging management system of plugged-in EVs based on user driving patterns in micro-grids - Ameli, Ali; Krauter, Stefan; Ameli, Mohammad Taghi; Moslehpour, Saeid (International Journal of Engineering Research & Innovation)

Photovoltaic yield prediction using an irradiance forecast model based on multiple neural networks - Durrani, Saad Parvaiz; Balluff, Stefan; Wurzer, Lukas; Krauter, Stefan (Journal of Modern Power Systems and Clean Energy)

Lifetime Extension of Photovoltaic Modules by Influencing the Module Temperature Using Phase Change Material - Weber, Daniel; Rafsan Jani, Mohammad Iffat; Grabo, Matti; Wallscheid, Oliver; Klaus, Tobias; Krauter, Stefan; Böcker, Joachim (World Conference on Photovoltaic Energy Conversion (WCPEC-7), 45th IEEE PVSC, 28th PVSEC, 34th EU PVSEC.)

Start-up factory Ghana: Creating an enabling environment for the dissemination of renewable energies - Klaus, Tobias; Nkrumah, I.; Donkor, M.K.E; Tamakloe, R.Y.; Ampong, F.K.; Krauter, Stefan (Proceedings of the ISES Solar World Congress 2017)

Minimizing storage costs by substituting centralized electrical storage by thermal storage at the end user, also suppling balancing power for grid operation - Krauter, Stefan; Prior, Dirk (Energy Procedia)
Many processes in industrial and domestic applications require heating or cooling at certain steps of a process. Even if the process itself cannot be shifted towards periods of high PV output (which would be favorable), the heating and cooling necessities can be carried out via an inexpensive thermal storage instead of a costly electrical storage. Examples are: distillation units, washing machines, dishwashers, coolers, freezers. The resulting “shiftability” of power consumption can be a business model by offering that availability of load dispatching on the balancing power market. An example using PCM as cooling storage for refrigerators that has been investigated: A focus of this paper is the use of that load shifting ability to provide balancing power. Another emphasis is on the protection of individual consumer data: To keep the state of use of each individual consumer (actually: interactive consumer or “prosumer”) anonymous, but still performing the sales of balancing power, the orders for load-dispatching can be transmitted via transmitted via a regional, non-individual broadcasting message within the GSM network. Demonstrating DSMs capacities, abilities and limits concerning domestic applications is an important task to prepare large-scale implementation and to convince stakeholders. To reaching that goal, several realistic DSM scenarios for cooling applications and freezers have been developed with the prerequisite that DSM activities are supposed to be without comfort losses and without restrictions for consumers while the limits for lower and upper temperature for food are maintained.
Keywords: DSM; load management; load shifting; PCM; thermal storage; balancing power

Performance of MERRA2 Data Compared to Floating LiDAR - Bendfeld, Jörg; Balluff, Stefan; Wübbeke, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2017)

Short-term wind speed and power prediction for offshore wind farms using neural networks - Bendfeld, Jörg; Balluff, Stefan; Krüger, J.; Krauter, Stefan (Proceedings of the DEWEK 2017)

Update on rankings of conversion efficiencies and energy yield of micro-inverters, including inverters for two PV modules - Bendfeld, Jörg; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017, S. 1477–1481)

Long-term performance of PV micro-inverters - Bendfeld, Jörg; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017, S. 1836–1840)

Advanced PV Module Hot Spot Characterisation - Krauter, Stefan; Wendlandt, S.; Süthoff, L.; Berendes, S.; Teubner, J.; Podlowski, L.; Berghold, J.; Grunow, Paul (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017)

Comparison of Conversion Efficiencies and Energy Yields of Micro-Inverters for Photovoltaic Modules - Krauter, Stefan (VDE-Proceedings of NEIS 2017 – Conference on Sustainable Energy Supply and Energy Storage Systems by IEEE-PES. Hamburg (Deutschland), 21.–22. September, 2017.)

Smart Charging Management System of Plugged-in EVs for Optimal Operation of Future Power Systems. - Krauter, Stefan; Ameli, Ali (VDE-Proceedings of NEIS 2017 – Conference on Sustainable Energy Supply and Energy Storage Systems by IEEE-PES. Hamburg (Deutschland), 21.–22. September, 2017.)

Minimizing storage costs: Simple and effective methods to match PV with grid load, including shift of holiday period - Krauter, Stefan (Proceedings of the 11th International Conference for Renewable Energy Storage, 14-16 March 2017, Düsseldorf, Germany.)

Introduction of an Advanced Method for Testing of Battery Charge Controllers for Off-Grid PV Systems - Khatibi, Arash; Bendfeld, Jörg; Bermpohl, Wolfgang; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017)

Testing and Analysis of Battery Charge Controllers for Off-Grid PV Systems - Khatibi, Arash; Bendfeld, Jörg; Bermpohl, Wolfgang; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017)

Offshore Metocean Station for Energy Purposes - Balluff, Stefan; Bendfeld, Jörg (Journal of Sustainable Development of Energy, Water and Environment Systems)

Einbindung von Oﬀshore Windenergie durch innovative Prognosemodelle und Speichertechnologien - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (14. Symposium Energieinnovation 2016)

Green Energy from the Ocean An overview on costeffectiv and reliable measuring systems - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (2015 International Conference on Renewable Energy Research and Applications (ICRERA))

Bestimmung der relevanten klimatologischen Parameter Oﬀshore - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Wissenschaftliche Verhandlungen 2016 der Deutschen Physikalischen Gesellschaft Regensburg)

Systemvergleich zur zeitlich und örtlich hochaufgelösten Einstrahlungsmessung - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Wissenschaftliche Verhandlungen 2016 der Deutschen Physikalischen Gesellschaft Regensburg)

Shadowing Investigations on Thin Film Modules - Krauter, Stefan; Wendtland, S.; Weber, T.; Berghold, J.; Grunow, Paul (Proceedings of the 31st European Photovoltaic Solar Energy Conference and Exhibition, München (Deutschland), 20.–24. Juni 2016, S. 2265–2270.)

Start-Up Factory Kumasi (Ghana) – Paderborn (Germany): Smart Tropical House KNUST, Kumasi, Ghana - Klaus, Tobias; Schmitz, E.A.; Klusmann, B.; Piper, M.; Krauter, Stefan; Rongen, L.; Gruber, R.; Nkrumah, I.; Ampong, K.; Donkor, M.; Tamakloe, R. (Proceedings of the 31st European Photovoltaic Solar Energy Conference and Exhibition, München (Deutschland), 20.–24. Juni 2016, S. 3048–3049)

Deviations of results for energy yield from efficiency rankings of micro-inverters - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 31st European Photovoltaic Solar Energy Conference and Exhibition, München (Deutschland), 20.–24. Juni 2016, S. 1508–1511)

Photovoltaics and the Energy System: Adaptation of layout and load. - Kazmerski, L.; Renne, D; Kazem, H.; Sopian, D.K.; Al-Bastaki, N.; Haji, S.; Mohd, D.; Othman, Y.H.; Hoffmann, W.; Krauter, Stefan; Swift-Hook, D.T.; Book, T. (Renewable Energy in the Service of Mankind Vol II)

Experimental study of phase change materials for photovoltaic modules: Energy performance and economic yield for the EPEX spot market - Japs, Ewald; Sonnenrein, Gerrit; Krauter, Stefan; Vrabec, Jadran (Solar Energy)

Short term wind and energy prediction for offshore wind farms using neural networks - Balluff, Stefan; Bendfeld, Jörg; Krauter, Stefan (2015 International Conference on Renewable Energy Research and Applications (ICRERA))

Measurement and Analysis of oﬀshore fog occurrences - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 95th AMS Annual Meeting)

Messtechnisches Prinzip eines neuen Einstrahlungsmessgerätes - Bendfeld, Jörg; Balluff, Stefan; Bermpohl, Wolfgang (Wissenschaftliche Verhandlungen 2015 der Deutschen Physikalischen Gesellschaft)

Performance of MERRA Data in Oﬀshore Wind Energy Applications - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Advanced Integration of Oﬀshore Wind Energy into the Grid System by Power to Gas - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Comparison of micro inverters based on practical analysis - Sadati, A.M.; Krauter, Stefan; Bendfeld, Jörg (2015 5th International Youth Conference on Energy (IYCE))

Effective large-scale PV integration: Methods to match load profile with actual PV output - Krauter, Stefan (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

Assessment of renewable energy resources in cameroon and special regards on energy supply - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))

Assessment of renewable energy resources and the use of hydro power for fluctuation compensation in Cameroon - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))

Cost, performance, and yield comparison of eight different micro-inverters - Krauter, Stefan; Bendfeld, Jörg (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

BOS cost reduction via direct PV charging of electrical vehicles - Krauter, Stefan (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

Stabilizing oﬀshore wind farm power feed-in via power to gas storage systems - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the Karlsruhe Institute of Technology (KIT) - Energy Science Technology 2015)

Discovering the potential for oﬀshore windfarms trough measurements - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the Karlsruhe Institute of Technology (KIT) - Energy Science Technology 2015)

Wind power forecasting for oﬀshore wind farms - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Oﬀshore wind energy development based on Merra data - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Oﬀshore metocean station for energy purposes - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Short term wind and energy prediction for oﬀshore wind farms using neural networks - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (EWEA Forecasting 2015 Technology Workshop)

Integration of Wind Energy in Power System—Modelling of a Market Oriented Energy Concept - Bouyraaman, Yassin; Bendfeld, Jörg; Breymann, Philipp; Krauter, Stefan (Renewable Energy in the Service of Mankind Vol I)

Integration of offshore wind energy into the grid system in Germany: Modelling of a market oriented energy provision - Bouyraaman, Yassin; Bendfeld, Jörg; Krauter, Stefan (14th IAEE European Energy Conference- Sustainable Energy Policy and Strategies in Europe, Rome, Italy, October 28-31, 2014)

Integration of wind energy in power systems: Modeling of a market-orientated energy concept - Bouyraaman, Yassin; Bendfeld, Jörg; Krauter, Stefan; Breymann, P. (Proceedings of the World Renewable Energy Congress WREC XIII, London, (UK), August 3-8, 2014)

Reduction of Offshore Wind farm power Feed-in ﬂuctuations via Power to Gas Storage Systems - Bouyraaman, Yassin; Bendfeld, Jörg (Solar 2014/Intersolar North America, San Francisco, July 6-10, 2014)

Advanced offshore Measurements for Windfarms - Bendfeld, Jörg; Balluff, Stefan (Solar 2014/Intersolar North America, San Francisco, July 6-10, 2014)

Solar Electric Power Systems. Second Edition - Krauter, Stefan

Measures to match load proﬁle with actual PV generation to achieve an effective integration into the energy system - Krauter, Stefan (Proceedings of the 6th World Conference of Photovoltaic Energy Conversion WCPEC 6, Kyoto (Japan), November 23-27, 2014)

Identiﬁcation and elimination of potential induced degradation (PID) at photovoltaic power plants - Krauter, Stefan (Proceedings of the 6th World Conference of Photovoltaic Energy Conversion WCPEC 6, Kyoto (Japan), November 23-27, 2014)

Performance and Yield Comparison of seven different Micro-Inverters. - Krauter, Stefan; Bendfeld, Jörg; Gohardehi, A.; Sadati, A. (Proceedings of the 6th World Conference of Photovoltaic Energy Conversion WCPEC 6, Kyoto (Japan), November 23-27, 2014)

Micro combined heat and power plants (micro-CHP) in combination with photovoltaics for autonomous local power and heat supply. - Krauter, Stefan; Bouyraaman, Yassin; Bendfeld, Jörg; Japs, Ewald (Proceedings of the 6th World Conference of Photovoltaic Energy Conversion WCPEC 6, Kyoto (Japan), November 23-27, 2014)

Photovoltaics and the Energy System: Adaptation of layout and load - Krauter, Stefan (Proceedings of the World Renewable Energy Congress WREC XIII, London, (UK), August 3-8, 2014)

An Optimized Load Frequency Control of a De-centralized Energy System Using Plug-in Electric Vehicles - Ameli, Ali; Ameli, H.; Krauter, Stefan; Hanitsch, Rolf (Proceedings of the MES-BREG 2014 Symposium “Innovating Energy Access for Remote Areas: Discovering untapped resources”, UC Berkeley (USA), April 10-12, 2014)

Energy-economic comparison of photovoltaic modules equipped with a layer of conventional and improved phase-change material - Japs, Ewald; Peters, S.; Sonnenrein, Gerrit; Krauter, Stefan (Proceedings of the 40th IEEE Photovoltaic Specialists Conference, Denver (USA), June 8-13, 2014)

Integration of PV into the Energy System: Challenges and Measures for Generation and Load Management - Krauter, Stefan; Japs, Ewald (Proceedings of the 40th IEEE Photovoltaic Specialists Conference, Denver (USA), June 8-13, 2014)

Plant layout modiﬁcations and load adaptation to integrate Photovoltaics in the energy system. - Krauter, Stefan (Proceedings of the 29th European Photovoltaic Solar Energy Conference and Exhibition, Amsterdam (The Netherlands), September 22-16, 2014)

Integration Erneuerbarer Energien: Herausforderungen und Maßnahmen im Erzeugungssektor und Lastmanagement - Krauter, Stefan (uwf Umwelt Wirtschafts Forum)

Comparison of Hot Spot Investigations under Laboratory and Field Conditions at Photovoltaic Modules - Wendlandt, Stefan; Krause, Melanie; Berendes, Sarah; Hanusch, Matthias; Drobisch, Alexander; Berghold, Juliane; Schoppa, Michael; Grunow, Paul; Krauter, Stefan (Proceedings of the 29th European Photovoltaic Solar Energy Conference and Exhibition, Amsterdam (The Netherlands), September 22-16, 2014)

Test Sequence Development for Evaluation of Potential Induced Degradation on Thin-Film Modules - Weber, T.; Berghold, J.; Heilmann, F.; Roericht, M.; Krauter, Stefan; Grunow, Paul (Proceedings of the 28th European Photovoltaic Solar Energy Conference and Exhibition, Paris (Frankreich)

Energiewende mit Sonnenstrom - Krauter, Stefan (Forschungsforum Paderborn, 16-2013, Februar 2013)

Technical investigation of a photovoltaic module with integrated improved phase change material - Japs, Ewald; Sonnenrein, Gerrit; Steube, Julia; Vrabec, Jadran; Kenig, E.; Krauter, Stefan (Proceedings of the 28th European Photovoltaic Solar Energy Conference and Exhibition, Paris (Frankreich))

Foundation Monitoring – An Overview of Methods and Measurement Solutions - Bendfeld, Jörg; Krieger, Jens (WINDFORCE 2013 Bremerhaven, 9. WAB Offshore-Windenergie Konferenz, Juni 2013)

Power to Gas – Eine andere Möglichkeit, Windstrom zu nutzen? - Bouyraaman, Yassin

Erstellung Klimaschutzkonzept der Stadt Paderborn unter Nutzung Erneuerbarer Energien, - Krauter, Stefan

7 YEARS METEOMAST AMRUMBANK WEST - Bendfeld, Jörg; Krieger, Jens (Europe’s Premier Wind Energy Event – EWEA 2013 Annual Event, Vienna, Austria, February 2013)

FOG MEASURING AND SELECTED OFFSHORE FOG OCCURRENCES FOR THE OFFSHORE WIND ENERGY - Bendfeld, Jörg; Balluff, Stefan; Bouyraaman, Yassin; Krieger, jens (Europe’s Premier Wind Energy Event – EWEA 2013 Annual Event, Vienna, Austria, February 2013)

FOUNDATION MONITORING FOR OFFSHORE WINDFARMS - Krieger, Jens; Bendfeld, Jörg (Europe’s Premier Wind Energy Event – EWEA 2013 Annual Event, Vienna, Austria, February 2013)

Optimisation of Offshore Wind farm Feed-in fluctuations via Power to Gas Storage Systems - Bouyraaman, Yassin; Bendfeld, Jörg (Europe’s Premier Wind Energy Event – EWEA 2013 Annual Event, Vienna, Austria, February 2013)

Measurements for PV-Module outdoor performance - Bendfeld, Jörg (Wissenschaftliche Verhandlungen 2013 der Deutschen Physikalischen Gesellschaft)

Foundation monitoring for offshore windfarms - Krieger, Jens; Bendfeld, Jörg (Wissenschaftliche Verhandlungen 2013 der Deutschen Physikalischen Gesellschaft)

Photovoltaics: Basics, Applications, Recent Developments - Krauter, Stefan

About the hot spot stability of ages silicon crystalline PV modules and materials - Wendlandt, Stefan; Berthold, Roman; Hanusch, Matthias; Drobisch, Alexander; Berghold, Juliane; Schoppa, Michael; Krauter, Stefan; Grunow, Paul (Proceedings of the 28th European Photovoltaic Solar Energy Conference and Exhibition, Paris (Frankreich))

Measurement of spectral-spatial distribution of global irradiance - Leers, Mathias; Preiss, Alexander; Ferretti, Nicoletta; Krauter, Stefan (2011 37th IEEE Photovoltaic Specialists Conference)

Suitable test procedure for electrical energy storage in PV operation mode – implementation and implication - Krauter, Stefan; Lang, o. (7th International Renewable Energy Storage Conference (IRES 2012), Berlin (Germany), 12.-14. November 2012)

PV 3.0 - Krauter, Stefan (Proceedings of the 27th European Photovoltaic Solar Energy Conference and Exhibition, Frankfurt a. M. (Germany), 24.-28. September 2012, pp. 4520-4522)